IMPLICAREA ADMINISTRAŢIEI PUBLICE LOCALE ÎN ASIGURAREA EGALITĂŢII DE ŞANSE ÎNTRE FEMEI ŞI BĂRBAŢI: STUDIU DE CAZ CONSILIUL RAIONULUI DONDUŞENI - Pastuh, Luminița (Editura USM, 2024)
The scope of this article resides in examining the involvement of local public administration in ensuring equal opportunities between women and men. The practical importance of the paper consists in the identification and implementation of the theoretical aspects addressed as well as the conclusions and recommendations highlighted in the context of the modernization and evolution of equal opportunities between women and men at the level of local public administration.
Keywords: egalitatea de gen